Marfan Syndrome and its cardiovascular repercussions - Aortic involvement (Research, Society and Development, 2025)
Marfan Syndrome (MS) is an autosomal dominant genetic disorder caused by mutation in the FBN1 gene, affecting fibrillin-1 formation and TGF-β signaling pathway, resulting in significant vascular alterations with high impact on morbidity and mortality. Objective: To review the literature on aortic involvement in MS, analyzing epidemiological aspects, clinical manifestations, therapeutic approaches, and prognostic factors, aiming at better understanding of the disease and its complications. Materials and Methods: Exploratory integrative review in four databases (BVS, SciELO, Google Scholar, and PubMed), following PICO methodology, with selection of 22 articles published between 2010-2025 in three languages, analyzed in six systematic stages. Results and Discussion: Aortic involvement affects 50-80% of Marfan Syndrome patients, manifesting as progressive dilation, aneurysms, and aortic dissection. Treatment involves preventive drug therapy and prophylactic surgery in specific cases. Conclusion: Aortic complications are the main cause of morbidity and mortality in MS, requiring continuous and individualized monitoring. Although therapeutic advances have increased survival, more than half of patients require constant monitoring and show high rates of post-surgical aortic involvement recurrence within a few years, highlighting the need for permanent surveillance and development of new treatment alternatives.